2005
DOI: 10.1016/j.jeconom.2004.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Modelling structural breaks, long memory and stock market volatility: an overview

Abstract: The main aim of this volume is to present key recent developments in the fields of modelling structural breaks, and the analysis of long memory and stock market volatility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(82 citation statements)
references
References 162 publications
(131 reference statements)
3
77
0
1
Order By: Relevance
“…This is standard in the structural change literature (e.g. Bai and Perron, 1998;Banerjee and Urga 2005). where T* is a compact subset of the R q Euclidean space.…”
Section: The Australian Rainfall Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This is standard in the structural change literature (e.g. Bai and Perron, 1998;Banerjee and Urga 2005). where T* is a compact subset of the R q Euclidean space.…”
Section: The Australian Rainfall Datamentioning
confidence: 99%
“…It is in fact a standard practice in the time series literature to remove the first and last 10% of observations to detect structural breaks (e.g. Bai and Perron 1998;Banerjee and Urga 2005).…”
mentioning
confidence: 99%
“…Granger and Hyung (2004) explained long memory phenomenon of asset returns by structural changes in GARCH and suggested that the time series with structural breaks can induce a strong persistence in the autocorrelation function and hence generate spurious long memory. Banerjee and Urga (2005) provide a comprehensive survey of the literature on both long memory and structural breaks, features of which are almost observationally equivalent.…”
Section: Introductionmentioning
confidence: 99%
“…Useful surveys can be found in Banerjee and Urga (2005) and Perron (2006). When extending the framework to a multivariate setting, the literature has shown that the cross sectional dimension can lead to better inference; for example, Bai, Lumsdaine and Stock (1998) show that the estimation of the changepoint in a VAR improves with the dimension of the VAR, due to the presence of cross sectional information.…”
Section: Introductionmentioning
confidence: 99%